Insan Kamil-Oriented Islamic Higher Education in Society 5.0: A Systematic Literature Review of Digital Transformation, Curriculum Integration, and Value-Based Islamic Leadership - Rizal, Muhammad; Ginanjar, Muhammad Hidayat; Nurhasan, Abdul Kodir; Dainuri, Muhamad Rifan (Jurnal Pendidikan Islam, 2025)
Purpose – This study formulates an integrative conceptual model of Islamic education at Islamic Religious Higher Education Institutions (PTKIS) in the Society 5.0 era by linking the orientation of insan kamil, digital technology, an Islamic curriculum, and value-based Islamic leadership to prevent the reduction of education into a merely technical process and the risk of dehumanization. Design/methods/approach – The study used a conceptual design through a systematic literature review for the period 2020 to 2025. Searches were conducted in Scopus, Google Scholar, DOAJ, and accredited national journal portals using keywords related to Islamic education, insan kamil, Society 5.0, PTKIS, and digital transformation. Of 412 identified articles, 62 articles passed the inclusion criteria through title screening, abstract screening, and full review. Data were analyzed using thematic analysis and descriptive mapping. Findings – The literature was dominated by conceptual studies or literature studies (40 of 62; 65%), indicating a gap in empirical evidence. Four main themes were identified: integration of Islamic curriculum and pedagogy with technology; Islamic digital leadership and governance; adoption of key technologies and ethical dilemmas; and character and spirituality formation in digital spaces. The synthesis produced an Input-Process-Output-Outcome framework grounded in Islamic values and spirituality, with outputs of spiritual-moral, critical-intellectual, digital-technological, and social-collaborative competencies that lead to insan kamil. Research implications – This model guides PTKIS in integrative curriculum design, strengthening digital literacy and artificial intelligence ethics, developing e-leadership based on amanah, adil, and ihsan, and collaboration of the campus, family, and community ecosystems.